The Cape Verde Project: Teaching Ecologically Sensitive and Socially Responsive Design - (:unkn) unknown (My University, 2014)
This dissertation chronicles an evolving teaching philosophy. It was an attempt to develop a way to teach ecological design in architecture informed by ethical responses to ecological devastation and social injustice. The world faces numerous social and ecological challenges at global scales. Recent Industrialization has brought about improved life expectancies and human comforts, coinciding with expanded civic rights and personal freedom, and increased wealth and opportunities. Unfortunately, industrialization also caused wide-scale pollution, mass extinctions and anthropogenic global climate change. Industrialization also reduced the earth's capacity to meet human resource demands - demands that are ever increasing due to population growth, urbanization and over-consumption. This dissertation develops an architectural theory based on ethics as a way for designers to engage the aforementioned issues. Architects play a pivotal role in shaping the environment, with the symbolic power and use of buildings, giving architects great sway in shaping social spaces and ecosystems. This important role necessitates in-depth curricula that address these problems. Architectural training focuses greatly on aesthetics and technical concerns, often at the expense of other equally important issues, such as ecological damage and social justice. In design education, design problems are often de-contextualized to avoid extraneous complications such as the economy or culture. Much of design education occurs with the study abroad and in the design studio. In the former, a grand tour of canonical buildings introduces architects to the precedents they learn to emulate. The latter is where instructors spend many hours in individual or small group interactions. The study abroad and the design studio provided ideal venues to address many of the current concerns beyond aesthetic and technical issues. These concerns include questions related to community engagement, social justice and the ecological effects of design. However, the complicated nature of these issues makes adequate curricula difficult to fashion. The challenge was to provide a framework for learning that was nimble, with wide-ranging curricula and adequate time for self-discovery. The framework included pedagogical content with contradictory claims and conflicting interests. The curricula were broad but provided attention to detail and deeper place knowledge, employed varied examples, experimentation and field work.
Keywords: Alternate Studio; Appropriate Technology; Ecological Crisis; Immersion; Social Justice; Sustainable Design